PROBLEMATIKA PENERAPAN HUKUM PERDATA ISLAM - Mhd. Khadafi Abdullah (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
This study examines the issues surrounding the implementation of Islamic civil law within society, particularly in the areas of marriage and waqf administration. Although Islamic civil law has been integrated into the national legal system through various regulations—such as the Marriage Law, the Religious Courts Law, and the Waqf Law—its implementation at the community level still encounters significant obstacles. Social realities indicate a gap between the normative provisions of Islamic law and the actual practices within society, which are still heavily influenced by local customs, traditions, and limited legal awareness. This research employs an empirical juridical method, which combines the examination of written legal norms with direct observation of legal practices within the community. Primary data were obtained through observations and interviews with nazhir, community leaders, KUA officials, and individuals who access religious legal services. Secondary data were collected from legislation, Islamic jurisprudence literature, legal books, and official documents related to waqf and marriage. Data were analyzed qualitatively through the processes of data reduction, data presentation, and interpretative conclusion drawing. The findings reveal that problems in waqf administration arise due to the low rate of waqf land certification, improper implementation of the waqf declaration (ikrar wakaf), strong community reliance on traditional leaders (ninik mamak) and nazhir, limited legal understanding, and the belief that waqf property cannot be contested. In marriage practices, recurring issues include incorrect determination of the marriage guardian (wali), lack of understanding regarding the role of the wali hakim, family conflicts, and inconsistencies in the recording of paternal identity. The prevalence of unregistered marriages (nikah siri) is driven by economic factors, limited awareness of the importance of marriage registration, and underage marriages. Meanwhile, unregistered divorces (cerai liar) create legal uncertainty, negatively affect the rights of women and children, and may lead to criminal violations. This study concludes that the primary factors hindering the proper implementation of Islamic civil law in society include low legal literacy, the strong influence of customary practices, insufficient public legal education by authorities, and weak community awareness of the importance of administrative legality. These findings are expected to contribute to improving the governance of Islamic legal services and enhancing the legal understanding of the community. Keywords : Islamic Civil Law, Waqf, Marriage Guardian, Unregistered Marriage, Unregistered Divorce.